The oak processionary moth: a new health hazard? - Rahlenbeck, Sibylle; Utikal, Jochen (The British journal of general practice, 2015)
Although a native of southern Europe, the thermophilic oak processionary moth (OPM, Thaumetopoea processionea ) is expanding its prevalence to encompass Central and Northern Europe. Roughly, over the past decade, the moth’s range has spread northwards and the species has now became established in the warmer regions of Northern France, the Netherlands, the UK, and Germany.1-3 In the UK, the moth occurs in Surrey and in parts of west London.4 It is thought that the northward progression is due to a decline in late spring frosts, resulting in a more synchronous egg hatch.4 Occurrence of caterpillar dermatitis has increased considerably, not only in gardeners, but also in people engaging in outdoor activities. The larvae of these caterpillars are equipped with fine, barbed hairs (setae, 0.2 mm), which can readily penetrate the human skin.5,6 One of the major issues with the hairs is that they readily detach and can then be blown via wind currents for considerable distances. The older larvae (fifth and sixth instars) are of particular concern as they can carry up to half a million of the urticating setae per caterpillar. The spines can be active for up to 10 years, posing a long-term threat to human health (Box 1). - - Box 1. - ### Key information